Nekotorye osobennosti reologiceskich svojstv krovi, lipidnogo obmena i gormonal'nogo statusa u sportsmenov silovych vidov sporta, ispol'zujuscich anaboliceskie steroidy - Melnikov, A. A.; Vikulov, A. D. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The purpose of the research was to study the state of rheological characteristics of blood, lipide structure and some hormones in athletes of power kinds of sports using anabolic steroids.